2021
DOI: 10.1126/sciadv.abg6677
|View full text |Cite
|
Sign up to set email alerts
|

Computational modeling of tau pathology spread reveals patterns of regional vulnerability and the impact of a genetic risk factor

Abstract: Neuropathological staging studies have suggested that tau pathology spreads through the brain in Alzheimer’s disease (AD) and other tauopathies, but it is unclear how neuroanatomical connections, spatial proximity, and regional vulnerability contribute. In this study, we seed tau pathology in the brains of nontransgenic mice with AD tau and quantify pathology development over 9 months in 134 brain regions. Network modeling of pathology progression shows that diffusion through the connectome is the best predict… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
44
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 38 publications
(49 citation statements)
references
References 61 publications
4
44
1
Order By: Relevance
“…This suggests a network-spreading phenomenon where focal pathology or perturbation propagates to connected regions, resulting in cortical abnormality that is correlated with the underlying connection patterns 14 . This interaction between local vulnerability and connectomic vulnerability has previously been reported in neurodegenerative syndromes where the trans-synaptic spreading of misfolded proteins appears to be guided and amplified by local gene expression 10,[71][72][73][74] . In other words, the poorer performance of connectivity predictors does not suggest that the white-matter architecture is less relevant to disease progression.…”
Section: Discussionsupporting
confidence: 60%
“…This suggests a network-spreading phenomenon where focal pathology or perturbation propagates to connected regions, resulting in cortical abnormality that is correlated with the underlying connection patterns 14 . This interaction between local vulnerability and connectomic vulnerability has previously been reported in neurodegenerative syndromes where the trans-synaptic spreading of misfolded proteins appears to be guided and amplified by local gene expression 10,[71][72][73][74] . In other words, the poorer performance of connectivity predictors does not suggest that the white-matter architecture is less relevant to disease progression.…”
Section: Discussionsupporting
confidence: 60%
“…Since these initial studies in non-transgenic mice, work has continued aiming to further characterise the patterns of spread. Recently, Cornblath and colleagues injected tau from AD brains into the brains of non-transgenic mice, and showed with network modelling analysis that diffusion through the connectome is the best predictor for tau pathology pattern, corroborating previous findings from others in the field [ 108 ]. This study also showed that retrograde, rather than anterograde spread, seems to dominate the spread of tau in the mouse brain [ 108 ].…”
Section: Tausupporting
confidence: 66%
“…For example, it has been recently shown that the tau accumulation rate in animal models is more related to local amplification than seed spreading ( 22 ). In this sense, several studies have suggested a specific cellular/molecular vulnerability driving (or modulating) the downstream neurodegeneration (and tau spreading) process ( 13 , 23 , 24 ). However, most studies have only assessed whether local regional vulnerability, such as the study of the cellular composition, genetic, and molecular environment for a specific region, present such selectivity to accumulate tau.…”
Section: Discussionmentioning
confidence: 99%